국회 청문회의 영향요인에 관한 연구 - 노재석 (의정논총, 14(2), 2019)
이 연구는 Walter J. Oleszek의 청문회 영향요인 분류를 원용하여 한국 국회의 청문회에영향을 미치는 것으로 추정되는 영향요인 분석틀을 고안하고 제20대 국회에서 개최된 3건의 회의록을 분석하여 영향요인을 검증하였다. 사례분석은 청문회 회의록과 관련 자료를대상으로 하였다. Walter J. Oleszek 7대 영향요인 중 위원장요인, 위원요인, 정당요인, 청문회준비·진행요인의 4대요인을 대분류요인으로 하고 하위요인으로 12개의 세부요인을 설정하여 분석의 틀을 구성하였다. 대분류요인인 위원장요인의 세부요인으로 지역구요인은 청문회 촉진요인으로 작용하지만, 위원장의 이념·소신 등 정치적 입장이나 리더십은 청문회에 미치는 영향이 크지 않은 것으로 나타났다. 위원요인 증 위원의 높은 회의출석률과 주제충실형 발언은 청문회 촉진요인으로 작용하였으나, 낮은 출석률과 정치성 발언은 방해요인으로 작용하였다. 정당요인 중 정당합의의 긴밀성이 촉진요인으로 작용했으며, 청문회준비·진행 요인 중 전문조사요원의 미충원, 사전조사 미실시, 요구자료 응답률 미정리, 준비기간의 적정성 미흡은 방해요인으로 작용하였다. This study seeks to analyze the influence factors on public hearings provided by the standing committee of the National Assembly of the Republic of Korea. The analytical framework was designed by using Walter J. Oleszek’s study. He described seven influence factors on public hearings of U.S. Congress but l classified four higher level factors and then set twelve sub-factors. Four higher level factors include the committee chair, committee members, bipartisanship, and the preparation and investigation made prior to the public hearings. The committee chair factor is composed of interests of constituencies, political attitude (personal ideas and belief) and leadership among committee members. Interests of constituencies encourage the committee chair to conduct the public hearing passionately as testified by examples of public hearings by standing committees of the National Assembly. Committee members are evaluated by participation rate of hearings and quality of questions at the hearing. Member’s good participation rates influence the incentive factors of public hearings. Sincere agreements of the public hearing between parties are factors that act as incentive factors of the hearings. Standing committees of the National Assembly neglected issuing documents of the conclusion of the public hearings, as usual. To effectively achieve the purpose of the public hearings, the standing committees should revise the bad practices and arrange the results of the conclusion of the public hearings on paper. KCI Citation Count: 0